Questions of Digital Power and the Re-animation of Critical Theory: An Interview with David Berry. (December 2014) - Beer, David
Questions of power can sometimes be sidelined in contemporary work on new media forms. David Berry's book Critical Theory and the Digital, which tackles such questions as power and capitalism, has recently been published by Bloomsbury. The following interview uses the book as a starting point for exploring questions of power in the context of digital media. It explores the potential role of critical theory for understanding contemporary media developments. The exchange explores some of the key themes and ideas from Berry's book whilst also focusing on how this project might develop in the future. As such, this is an interview that is concerned with questions of digital power and the possibility of re-animating critical theory.